Model – model komunikasi bisnis sebagai upaya meningkatkan penjualan produk vivelle di shan hair beauty care - Hakim, Abdul (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
From marketing to business communications, corporate strategy can be found in a variety of areas. Cosmetics companies are also feeling the heat of market competition. One of the most popular cosmetic products on the market is perfume. Shan Hair and Beauty Care is a retailer that sells a variety of beauty products such as hair care, perfume, and body care, with Vivelle being the perfume offering. The purpose of this research is to find out how the business communication strategy carried out by Shan Hair and Beauty Care to increase the number of sales from Vivelle. This research is a descriptive study with qualitative data. Observation, interview, and documentation were chosen as data collection techniques with the research location of Shan Hair and Beauty Care, followed by the owner of Shan Hair and Beauty Care and ten Vivelle customers. The data analysis technique used is data reduction analysis, then the data presentation technique is used to present the data. To test the validity of the data, it used triangulation of sources and theories. The Shan Hair and Beauty Care business communication strategy is highly effective, according to these findings. The business communication strategy is an important spearhead for the success cycle of Shan Hair and Beauty Care, as well as a strategy in facing various intense competition, especially in the selling price of products. The development of a strategy in business communication that matches the sales of Vivelle products at Shan Hair and Beauty Care can reach its glory. Shan Hair and Beauty Care values customer service. Sales strategy for Shan Hair and Beauty Care is a strategy in short-term market penetration that aims to attract consumers and distributors through business communication.Â Keywords: Strategy; Business Communication; and Sales